Profiling of a panel of radioresistant prostate cancer cells identifies deregulation of key miRNAs - McDermott, Niamh (Clin Transl Radiat Oncol, 2017)
BACKGROUND: miRNAs are increasingly associated with the aggressive phenotype of prostate tumours. Their ability to control radiobiologically-relevant cellular processes strengthens their potential as novel markers of response to radiation therapy. PURPOSE: To identify miRNAs associated with increased clonogenic survival following radiation exposure. MATERIAL AND METHODS: The miRNA expression profiles of a panel of 22RV1 cells with varying levels of radiosensitivities (hypoxic H-22Rv1 cells, RR-22Rv1 cells derived from WT-22Rv1 cells through 2-Gy fractionated repeated exposure, the associated aged matched cells (AMC-22Rv1) and the WT-22Rv1 cell lines) were generated and cross-analysed to identify common miRNAs associated with a radioresistant phenotype. RESULTS: Increased clonogenic survival following irradiation was associated with significant modifications in miRNA expression pattern. miR-221 (up) and miR-4284 (down) in RR-22Rv1 and MiR-31 and miR-200c in AMC-22Rv1 were the most uniquely significantly deregulated miRNAs when compared to WT-22Rv1 cells. miR-200c ranked as the most downregulated miRNAs in hypoxic, when compared to RR-22Rv1 cells. miR-200a was the only differentially expressed miRNA between RR-22Rv1 and AMC-22Rv1 cells. miR-210 yielded the highest fold change in expression in H-22Rv1, when compared to WT-22RV1 cells. CONCLUSION: This study identifies candidate miRNAs for the development of novel prognostic biomarkers for radiotherapy prostate cancer patients.